The Decline of Islamic Civilization In The Transition Era From the Ottoman Sultanate To The Republik of Turkey 1908-1938: A Historical and Socio-Political Analysis - Aorta Abdillah A'laa; Ahmad Kholil; Fadil S. J (Batuthah: Jurnal Sejarah Padaban Islam, 2026)
The decline of Islamic civilization in the early twentieth century cannot be separated from the dynamics of political and social transformations that took place in Anatolia. The transitional period from the caliphate system to the modern nation-state marked a crucial turning point that signified fundamental changes in the structure of power, identity, and the social life of Muslim communities. This study aims to explain how secularization reshaped the institutional position of Islam within the structure of the modern state. The research employs a qualitative method with a descriptive-analytical approach based on library research of historical works and modern Turkish political theory. The findings indicate that what is referred to as the “decline of Islamic civilization” in this context does not denote the disappearance of religiosity among Muslim societies, but rather the reduction of Islam’s normative and institutional role within the state’s system of legitimacy. Legal, educational, and religious-symbolic reforms during the republican era relocated Islam from the foundation of public political authority to a sphere regulated by the state. This transformation marked a paradigmatic shift from theosentric-imperial legitimacy to national-secular legitimacy. Thus, decline is understood as a restructuring of authority and civilizational orientation, rather than merely a political downfall or a dichotomy between Islam and modernity.